Upgraded photometric system on the 85-cm telescope at Xinglong station. (August 2018) - Bai, Chun-Hai; Fu, Jian-Ning; Li, Tao-Ran; Fan, Zhou; Wu, Jiang-Hua; Zhao, Yong; Zeng, Xian-Qun; Zhang, Wen-Zhao; Qiu, Peng; Feng, Guo-Jie; Jiang, Xiao-Jun
Abstract: The 85-cm telescope at Xinglong station is a prime focus system that operates well with high science outputs. The telescope has been upgraded since 2014 with a new corrector, and new filters and camera, which are provided by Beijing Normal University. The filter set is the Johnson-Cousins UBVRI system. We report the test results of the new system including bias, dark current, linearity, gain and readout noise of the CCD camera. Then we derive accurate instrumental calibration coefficients in UBVRI bands with Landolt standard stars during photometric nights. Finally, we give the limiting magnitudes with various exposure times and signal-to-noise ratios for observers as references.